2015
DOI: 10.2105/ajph.2015.302671
|View full text |Cite
|
Sign up to set email alerts
|

Flu and Finances: Influenza Outbreaks and Loan Defaults in US Cities, 2004–2012

Abstract: Overall, it appears there is a relationship between exogenous health shocks (such as influenza) and credit default. The results suggest that consumer finances could benefit from policies that aim to reduce the financial shocks of illness, particularly for vulnerable borrowers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Only a few studies have linked credit to individual or population-based health conditions [ 40 – 44 ], and no studies have linked credit to health after cancer. One ecological study found small but significant increases in city-wide influenza severity among those who fell behind on debt payments, which would influence credit quality [ 43 ]. If an economic shock [ 43 , 45 ] due to an acute disease like the flu is associated with consumer credit, the shock due to management of a chronic disease and adverse events arising from it could have larger and sustained impacts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies have linked credit to individual or population-based health conditions [ 40 – 44 ], and no studies have linked credit to health after cancer. One ecological study found small but significant increases in city-wide influenza severity among those who fell behind on debt payments, which would influence credit quality [ 43 ]. If an economic shock [ 43 , 45 ] due to an acute disease like the flu is associated with consumer credit, the shock due to management of a chronic disease and adverse events arising from it could have larger and sustained impacts.…”
Section: Introductionmentioning
confidence: 99%
“…One ecological study found small but significant increases in city-wide influenza severity among those who fell behind on debt payments, which would influence credit quality [ 43 ]. If an economic shock [ 43 , 45 ] due to an acute disease like the flu is associated with consumer credit, the shock due to management of a chronic disease and adverse events arising from it could have larger and sustained impacts. To assess how an economic shock due to chronic disease might be associated with credit quality, this exploratory analysis assessed the relationships between current self-reported consumer credit quality and (a) economic burden since cancer, and (b) current mental and physical health in a sample of women who had experienced the chronic disease of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Credit scores represent a person’s financial situation, and low credit score has been linked to both worse outcomes for both acute and chronic disease (14). In the United States, credit scores are numeric estimates of an individual’s likelihood of paying debts on time (5) based on past payment behavior, current credit utilization, history or length of credit use, new accounts and credit inquiries, and mix of credit in use (6).…”
mentioning
confidence: 99%
“…For example, a previous study suggesting higher credit scores with lower cardiovascular disease risk found that education and behavioral factors explained 45% of the relationship between credit and health (1). A study suggesting higher credit default rates coincided with higher influenza rates posited that illness represents an economic shock that disrupts income and financial security, and might influence credit scores (4). Yet, studies have not assessed how credit scores are linked to measures of financial security or socio-economic position (7).…”
mentioning
confidence: 99%
“…(2) Area-level consumer credit may also reflect areas where disease prevalence is high, especially when costs to manage or treat those chronic diseases may lead to populations who experience higher medical costs. For example, one ecological study in the USA found small but significant increases in city-wide influenza severity with a higher area-level credit card and mortgage default rates 4. The authors attributed this to the increased likelihood of consumer credit borrowing in areas with higher disease rates.…”
Section: Resultsmentioning
confidence: 99%